2011
DOI: 10.1002/ar.21368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Habitat Light Intensity on Mammalian Eye Shape

Abstract: Many aspects of mammalian visual anatomy vary with activity pattern, reflecting the divergent selective pressures imposed by low light and high light visual environments. However, ambient light intensity can also differ substantially between and within habitats due to differences in foliage density. We explored the effects of interhabitat and intrahabitat variation in light intensity on mammalian visual anatomy. Data on relative cornea size, activity pattern, and habitat type were collected from the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 54 publications
2
39
0
1
Order By: Relevance
“…Eye morphology has previously been shown to relate to time of activity (i.e. nocturnal, crepuscular or diurnal, [33], [34], [35], [36]), while eye position (measured as distance to the mandibles) may be determined by the degree of predatory behaviour [25], [37]. We show here that habitat complexity also determines the success of species, based on the position of their eyes.…”
Section: Discussionmentioning
confidence: 65%
“…Eye morphology has previously been shown to relate to time of activity (i.e. nocturnal, crepuscular or diurnal, [33], [34], [35], [36]), while eye position (measured as distance to the mandibles) may be determined by the degree of predatory behaviour [25], [37]. We show here that habitat complexity also determines the success of species, based on the position of their eyes.…”
Section: Discussionmentioning
confidence: 65%
“…For example, Veilleux and Lewis [2011] recently found that mammalian eye shape varied predictably with ambient light intensity in different habitat types. In particular, mammals from more open habitats exhibited smaller relative cornea sizes compared to species from closed canopy forests.…”
Section: Ecology and Mammalian Visual Acuitymentioning
confidence: 99%
“…Therefore, it appears that, in terms of gross morphology, the eyes of the 5 hummingbird species investigated here are adapted for diurnal vision. In general, ratios that measure the size of the cornea relative to the eye, such as the C:T ratio, have proven to be highly correlated with activity pattern in birds [Hall and Ross, 2007;Lisney et al, 2012bLisney et al, , 2013b, nonavian reptiles [Hall, 2008], and mammals [Hughes, 1977;Kirk, 2004Kirk, , 2006Veilleux and Lewis, 2011]. Higher ratios equate to an enlarged cornea relative to the size of the eye, which serves to increase the amount of light that can enter the eye when the pupil is maximally dilated and is thus hugely advantageous for nocturnal species active at low light levels [Walls, 1942;Land and Nilsson, 2002;Kirk, 2006].…”
Section: Eye Morphologymentioning
confidence: 99%
“…We have previously employed this approach successfully to investigate the visual systems of gamefowl [Lisney et al, 2012a], owls [Lisney et al, 2012b], waterfowl [Lisney et al, 2013a], and vultures [Lisney et al, 2013b]. Eye morphology, as determined from basic measurements of cornea size relative to eye size, has proved to be useful when comparing eyes from different species because relative cornea size is an excellent predictor of activity pattern in birds [Hall and Ross, 2007;Lisney et al, 2012a, b] as well as other vertebrates [Walls, 1942;Hughes, 1977;Kirk, 2004Kirk, , 2006Hall, 2008;Veilleux and Lewis, 2011]. Similarly, studies of retinal topography are informative because they serve to both identify and quantify specialized areas of high neuron density (i.e.…”
Section: Introductionmentioning
confidence: 99%